Sediment characteristics across the Rio Grande Delta upstream of Elephant Butte Reservoir (July 2021-September 2022) - Abigail Eckland; Irina Overeem; Brandee Carlson (PANGAEA, 2023)
Sediment and sediment-water samples were collected within the Rio Grande channel and its delta upstream of Elephant Butte Reservoir during four field campaigns spanning between July 2021 and September 2022: (1) July 4-6, 2021, (2) March 20-22, 2022, (3) May 6-8, 2022, and (4) September 16-18, 2022. Sediment analyses were conducted on four sample types: (1) suspended sediment, collected from water in the Rio Grande channel at two-thirds of the total channel depth below the water surface, (2) bed material, from the Rio Grande channel, (3) shallow stratigraphic column samples, collected from 0 to 0.5 meters in depth in the Rio Grande Delta, and (4) Elephant Butte Reservoir water samples, collected near the mouth of the Rio Grande at the top (0.5 m below the water surface) and bottom (0.5 m above the bed) of the water column. The sediment analyses reported herein include computing Suspended Sediment Concentration (SSC) for sample types 1 and 4, and Organic Matter Content (%) for all sample types (1-4). SSC was determined by measuring the water volume of the sample, then freeze-drying and weighing the mass of sediment to obtain a concentration (kg/m^3). OM% was determined by performing Loss on Ignition (LOI) on all sample types (1-4), which removes organic material from the sample through exposure to high temperatures in a muffle furnace. The purpose of these analyses was to characterize the amount and type of sediment transported and deposited within Elephant Butte Reservoir and its delta during different times of the year.
In: Eckland, A et al. (2023): Sediment, hydrologic, and temperature data collected from the Rio Grande Delta upstream of Elephant Butte Reservoir, NM (July 2021-September 2022) [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.961886